The Use of Formal and Informal Language Varieties in Internal Communication of the Deli Serdang Regency DPRD - Putri Puspitasari; Nurul Nazma Zafira; Faradila Fairuz Alsha; Nurisa Nabila Utami; Dewi Nurmala (West Science Social and Humanities Studies, 2026)
Internal communication in government institutions requires the appropriate use of language varieties according to communicative contexts. This article aims to describe the use of formal and informal language varieties in the internal communication of the Regional House of Representatives (DPRD) of Deli Serdang Regency based on Practical Work Experience (PKL). A qualitative descriptive method was applied through direct observation and documentation of spoken utterances. The findings show that formal language is used in official and institutional activities, while informal language is used in daily work communication for coordination and task instructions. These findings indicate that language use within the DPRD is contextual and adaptive.